Modeling of Copper Adsorption on Mesoporous Carbon CMK-3: Response Surface Design - Zeinab Ezzeddine; Isabelle Batonneau-Gener; Yannick Pouilloux (ChemEngineering, 2018)
CMK-3 mesoporous carbon was nanocast from SBA-15 silica. The obtained carbon was characterized by nitrogen sorption isotherms, X-ray diffraction and transmission electron microscopy (TEM). The batch adsorption tests were done at constant pH taking into account the initial metal ion concentration, adsorbent mass and temperature. A statistical study using a response surface design method was done to develop a mathematical model to predict copper adsorption on CMK-3 as a function of the mentioned experimental factors. It was found that all these parameters are significant, and copper concentration has the greatest effect on adsorption among them. Moreover, the obtained model proved to be adequate in predicting copper adsorption on CMK-3 and its performance under different experimental conditions.